The attraction of Zonocerus variegatus (Orthoptera: Pyrgomorphidae) to different types of lure - Babatunde Idowu, A (2001)
Zonocerus variegatus is a common grasshopper in parts of west and equtorial Africa.The distribution in Nigeria extends from the lowland rainforest zone to the savannah in the north. The influence of lure on the behaviour of grasshopper inside cages (120 insect per cage) was investigated. Nymphs and adults of Zonocerus variegatus responded positively to intact leaves, crushed leaves and inflorescence of the common compositae weed Chromolaena odorata inside muslin bags, and intact plants. There were significant differences in the attraction recorded for starved nymphs, fed nymphs and starved adults. Attraction was more to intact leaves and is by olfaction. The increase in the attraction of starved nymphs is time dependent. Attraction to plant parts ceased after the plants were dried for 24 and 48 hours at room temperature and when plants were placed in transparent polythene bags. Gut motility and gut activity were higher during the day than at night. Nymphs, adults and egg pods placed separately inside muslin bags were not attractive to adults or nymphs.